2015
DOI: 10.1002/pssb.201552027
|View full text |Cite
|
Sign up to set email alerts
|

Large diameter multiwall nanotubes of MgB2: Structural aspects and stability of superconducting nanotubular magnesium boride

Abstract: Based on a theoretical study, we demonstrated that magnesium boride nanotubes can reach the same stability as bulk MgB 2 structure. However, most stable nanotubular forms are not structurally derived from mixed triangular-hexagonal structural motifs of a single layer sheet, which is thought to be the 2D precursor form of all boron nanotubes. MgB 2 multiwall nanotubular structures that are derived from multilayer MgB 2 slabs with honeycomb Bnetworks in hexagonal lattices are more stable. The results of an ab in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…More specific arrangement of the theory toward superconductivity is available in the form of open access papers [52][53][54] in physical journals. On semiempirical level, the theory was applied to study superconductivity 48,[55][56][57][58][59][60][61][62] in anti-adiabatic state for different groups of superconductors or to study some spectral properties of superconductors, e.g. ARPES 55,56 or pump-probe spectroscopy of relaxation processes in superconductors 62 .…”
Section: Discussionmentioning
confidence: 99%
“…More specific arrangement of the theory toward superconductivity is available in the form of open access papers [52][53][54] in physical journals. On semiempirical level, the theory was applied to study superconductivity 48,[55][56][57][58][59][60][61][62] in anti-adiabatic state for different groups of superconductors or to study some spectral properties of superconductors, e.g. ARPES 55,56 or pump-probe spectroscopy of relaxation processes in superconductors 62 .…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that the electronic and thermodynamic properties of the system in a stabilized anti-adiabatic state correspond to the properties of that particular system in a superconducting state. Recently, this theory has been applied for the prediction of superconductivity in new boron-based nanotubular materials [33,34]. Theoretical study of anti-adiabatic state transition in MgB 2 has been published [25], with the calculated parameters being in good agreement with experiments [35,36].…”
Section: Model Of Mgb 2 For the Study Of Excited State Relaxation Dynmentioning
confidence: 93%
“…As a kind of 1D carbon nanomaterials because of its unique properties and low cost, multiwalled carbon nanotubes (MWNTs) show great potential to be used in the field of nanoelectronic, superconductors, electrochemical capacitors, micro‐supercapacitors, nanowires, and energy harvesting . Herein, we reported a novel strategy to fabricate functionalized MWNTs/PI nanocomposite aerogels.…”
Section: Formulation and Density Of Pi And Pi/mwnts Nanocomposite Aermentioning
confidence: 99%